ANALISIS FINANSIAL AGROINDUSTRI BERBASIS DAGING TIRUAN BERBAHAN DASAR TEPUNG BIJI DURIAN (Durio zibethinus Murr.), ISOLAT PROTEIN KEDELAI DAN AIR - Dicki Hardi Wantoro; Herlina Herlina; Triana Lindriati (JURNAL AGROTEKNOLOGI, 2015)
Meat analog is usually made of isolated soy protein and water. Durian (Durio zibethinus Murr.) seeds flour contained carbohydrate to improve its texture and can decrease blood cholesterol. This potential shoving of meat analog-based agroindustry. One of method to feasibility agroindustry identification using finansial feasibility analysis. The purpose of this research is to determine finansial feasibility and sensitivity analysis of meat analog agroindustry. The result showed meat analog agroindustry is a decent executed NPV 447.775.852, IRR of 28,56%, B/C Ratio of 1,35, the Payback Period for 2 year 5 months 12 days. To get the profit, meat analog production must be above 21.465 packaging and sales value of more than Rp. 103.033.458,00. In the sensitivity analysis of meat analog agroindustry is viable when there is an increase in variable cost and is not viable when a decrease in the selling price of 15%.Keywords: meat analog, financial analysis, sensitivity